The new Italian water tariff method: A launching point for novel infrastructures or a backwards step?. (June 2015) - Romano, Giulia; Guerrini, Andrea; Campedelli, Bettina
Abstract: In Italy recently the regulatory authority for electricity, gas and the water industry was mandated to design a new tariff method more consistent with EU standards of 'full cost recovery' and the 'polluter pays' rules. This paper attempts to highlight the strengths and limitations of this new method, its actual effects on tariffs, financial plans and utilities' investment policy, compared to the previous method, with a focus on the effects of the tariff method for both users and utilities. A case study was selected and this included the biggest water utility controlled by the local water authority in Verona province. Highlights: We examine the differences between the tariff methods applied to the Italian water industry. We investigate the effects on users and water utilities of the new tariff method. Wide variances arise between the financial plans drafted with the two methods. The main effect of the new method is a relevant increase of costs and revenues. A higher expenditure incurred by users for water services has been found.